A hénôsis plotiniana como exaltação da oralidade dialética de Platão - Marques, Rudinei dos Santos (2016)
This work aims to show, from the Dialogues, the Letters and the indirect tradition of Plato, as well as from the Enneads of Plotinus, the importance that the unwritten doctrines exercised in the constitution of plotinian neoplatonism, and thus that there was not a radical break between this movement and the platonic ontology, but the development and re-articulation of philosophical concepts already present in the written work of Plato and complemented by the intra-academic teaching, to which Plotinus had access through the reading of Aristotle's Metaphysics, as evidenced by Vita Plotini and the Enneads theirselves. In this perspective, the neoplatonic hénôsis can be understood as an exaltation of Plato’s unwritten doctrines.